Subjective Perception of the Realities of Modern Physical Education Classes Among Physical Education Teachers and Students in Higher Grades - Edita Maciulevičienė; Jolanta Gedvilienė (Lithuanian Sports University, 2018)
Background. Intense changes in national education require new students' teaching technologies in physical education. There are a number of studies, published books or articles on the topics of modern physical education classes and they provide guidance for teachers, but we believe that there is a lack of modernity in the reality of physical education, still focusing on sports lessons avoiding non-traditional content of the lessons. Research aim was to reveal the subjective opinions of physical education teachers and students in higher grades about the realities of modern physical education classes. Methods. The sample included physical education teachers (n = 33) and 10-11 th  grade students (n = 324), who were selected applying the convenience sampling strategy from Kaunas city schools. The research employed a questionnaire by Pate, Corbin, and Pangrazi (1998), and some more questions of interest to the researchers were added.  The  survey  was  conducted  in  spring  of  2012.  The  research  participants  were  surveyed  in  their  schools during the classes with the consent of physical education teachers and students and with the permission of school administration received in advance. Results. Students more often pointed out the lack of attention to individual work and its implementation, just one-fifth of the students indicated that lessons met their needs and physical education teachers sometimes met modern requirements, showing sincerity, respect, etc. The survey showed that physical education classes were still largely dominated by sports and movement skills, and only sometimes by the non-traditional or healthy lifestyle. Teachers more often than students highlighted the progress and initiative criteria. The most common means of discipline for students in physical education were a whistle and loud shouting. Conclusion.  Physical  Education  teachers  tend  to  subjectively  better  evaluate  the  contemporary  realities  of physical education classes compared to students. Teachers more often indicated that they applied independent work in their lessons, and thought that the lesson content met the needs of the students and led enough to unconventional physical activity and healthy lifestyle. Students more often pointed out that teachers never assessed them according to their progress in the development of their physical qualities and knowledge during lessons. In the opinions of teachers and students, physical fitness test results are still common evaluation criteria in the lessons. Keywords: lesson, physical education, modern, teachers.